Smokejumpers of the Civilian Public Service in World War II : conscientious objectors as firefighters for the National Forest Service - Cottrell, Robert C., 1950- (McFarland & Co., 2006)
"This is the story of Civilian Public Service smokejumpers, who battled against dangerous winds, searing heat, and devastating fires from 1943 until 1945"--Provided by publisher.